PREGNANCY AND DELIVERY IN PATIENTS WITH MESENHYMAL DYSPLASIAS (MARFAN SYNDROME, EHLERS-DANLOS SYNDROME, HEREDITARY HEMORRHAGIC TELANGIECTASIA) - L. S. Radetskaya; A. D. Makatsariya (Акушерство, гинекология и репродукция)
Aim. To study the pregnancy course and delivery outcome in patients with mesenchymal dysplasias (Marfan syndrome, Ehlers-Danlos syndrome (EDS), Hereditary hemorrhagic telangiectasia (HHT).Material and Methods. 56 pregnant women with mesenchymal dysplasias (23 with Marfan syndrome, 22 with Ehlers-Danlos syndrome, 11 with hereditary hemorrhagic telangictasia (HHT) were examined in specialized cardiological maternity house by using physical examination, routine laboratory tests, hemostasiological tests, ECG, echocardiography, MRI, radiology, pulse oximetry.Results. All patients had hemorrhagic complications various localizations; 18 women with Marfan syndrome developed increasing of mitral regurgitation, 10 – aortic insufficiency, 13 – mitral valve insufficiency. 1 patient with Marfan syndrome was died due to aortic dissection in 45 day after delivery. Pulmonary arteriovenous malformations were visualized in 10 patients with HHT; the symptoms of hypoxemia developed in 6 HHT patients and were result of right-to-left. One patient with HHT developed the symptoms of compression of vena cava inferior due to aneurism of truncus brachiocephalicus. 40 patients had abnormal hemostasiological tests (platelet dysfunction – in 38 patients; DIC syndrome – in 31). Cesarean section was performed in 53 patients. Vaginal delivery (3 patients with EDS) was complicated by massive postpartum hemorrhage and deep vaginal tears.Conclusions. Patients with mesenchymal dysplasias have a great risk of different complications, during pregnancy and delivery and require the multidisciplinary care and repeated hemostasiological testing. Cesarean section is the preferred method of delivery in such patients.